“KEBIASAAN MINUM JAMU UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU NIFAS DI DESA LARANGAN TOKOL KABUPATEN PAMEKASAN” - Zahroh Zahroh; Eko Mulyadi; Aulia Aulia (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2023)
Exclusive breastfeeding coverage in 2019 in Larangan Tokol village, wich was 43 babies (0,75%). This figure is still far from the Pamekasan Regency exclusive breastfeeding target in 2019, wich 57,3%. This is due to the community’s habit of giving additional food before the baby is 6 months old and the mother’s complaints due to low milk production. One of the postpartum mother’s efforts to increase the production of a small amount of breast milk is to consume jamu pejje because it countains lactogogue which can stimulate the hormone prolactin in the production of breast milk. The purpose of this study was to determine the habit of drinking herbal medicine to increase the production of breast milk in Larangan Tokol village, Pamekasan Regency. This research is a qualitative research with a phenomenological approach. Data were collected through interviews and observations of all postpartum mothers in Larangan Tokol village, Pamekasan Regency in November 2021 who met the inclusion and exclusion criteria. The validity of the data was validated by triangulating the data to 6 triangulated informants. The results showed that all informants drank jamu pejje to increase breast milk production during their puerperium. 6 of them drink in powder form and 4 others drink in mixed form (powder and chopped) every day for 40 days of puerperium. The conclusion of this study is that postpartum mothers in Larangan Tokol village, Pamekasan Regency have the habit of drinking herbal medicine to increase breast milk production.